Perovskite quantum dot glass and preparation method and application thereof

By inducing the in-situ growth of CsPbX3 quantum dots in perovskite quantum dot glass, the problem of easy decomposition of perovskite quantum dots is solved, and the effect of high stability and efficient ultraviolet detection is achieved.

CN119707303APending Publication Date: 2025-03-28CHINA BUILDING MATERIALS ACADEMY CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411624602.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Perovskite quantum dots are easy to decompose after contacting water and oxygen, limiting their wider application. How to improve their stability has become an important issue.

Method used

By preparing a specific proportion of glass raw materials, including SiO2, H3BO3, ZnO, Cs2CO3, PbX2 and NaX, melting and annealing treatment are carried out to induce the CsPbX3 quantum dots to grow in situ within the glass matrix to form perovskite quantum dot glass.

Benefits of technology

It improves the long-term stability of perovskite quantum dots, avoids the decomposition problem caused by contact with water and oxygen, and has high luminescence intensity, high quantum yield and wide excitation spectrum, which is suitable for efficient detection of ultraviolet detectors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119707303A_ABST
    Figure CN119707303A_ABST
Patent Text Reader

Abstract

The invention provides perovskite quantum dot glass as well as a preparation method and application thereof, and the preparation method comprises the following steps: preparing glass raw materials according to the following formula in percentage by mass of oxides: 30-40% of SiO2; 20 to 30 percent of H3BO3; 15%-20% of ZnO (zinc oxide); 10% to 15% of Cs2CO3; 5%-10% of PbX2; and 5% to 10% of NaX; wherein X is at least one of Cl, Br and I. The preparation method comprises the following steps: melting a glass raw material, annealing at 350-450 DEG C, and inducing CsPbX3 quantum dots to grow in situ in a glass matrix to obtain the perovskite quantum dot glass. In the perovskite quantum dot glass prepared by the invention, the outer ring of each perovskite crystal grain is wrapped by the amorphous glass component, so that the contact with water and oxygen is effectively avoided, and the long-term stability of the perovskite quantum dot is improved; meanwhile, the perovskite quantum dot glass also has high luminous intensity, high quantum yield and wide excitation spectrum, the perovskite quantum dots can be excited to emit light in an ultraviolet band, and the perovskite quantum dot glass can be applied to an ultraviolet detector to efficiently detect ultraviolet light.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of ultraviolet detection technology, and in particular to a perovskite quantum dot glass and a preparation method and application thereof. Background Art

[0002] Perovskite quantum dots are currently excellent optoelectronic luminescent materials with high photoluminescence quantum yield (PLQY), excellent color purity and tunable band gap. Perovskite quantum dots have attracted widespread attention in recent years due to their simple synthesis, high defect tolerance and excellent optical properties.

[0003] The solution method is a common method for synthesizing perovskite quantum dots, but the perovskite quantum dots synthesized by this method are easily decomposed after contact with water and oxygen, limiting their wider application.

[0004] Therefore, how to improve the stability of perovskite quantum dots is of great significance. Summary of the invention

[0005] The main purpose of the present invention is to provide a perovskite quantum dot glass and a preparation method and application thereof. The technical problem to be solved is how to provide a highly stable perovskite quantum dot glass which has high stability and is not easy to decompose, thereby being more suitable for practical use.

[0006] The purpose of the present invention and the technical problem to be solved are achieved by adopting the following technical solutions. According to a method for preparing perovskite quantum dot glass proposed in the present invention, the steps include:

[0007] (1) preparing glass raw materials; the glass raw materials include, by oxide mass percentage, 30-40% SiO2; 20-30% H3BO3; 15-20% ZnO; 10-15% Cs2CO3; 5-10% PbX2; and 5-10% NaX; wherein X is at least one of Cl, Br and I;

[0008] (2) melting the aforementioned glass raw materials to obtain a glass melt;

[0009] (3) pouring the aforementioned glass melt into a mold to obtain a precursor glass; and,

[0010] (4) The aforementioned precursor glass is annealed at 350-450° C. to induce in-situ growth of CsPbX 3 quantum dots in the glass matrix to obtain perovskite quantum dot glass.

[0011] The purpose of the present invention and the solution to its technical problems can be further achieved by adopting the following technical measures.

[0012] In some embodiments, according to the aforementioned method for preparing perovskite quantum dot glass, in step (2), the melting temperature is 1000-1100°C.

[0013] In some embodiments, according to the aforementioned method for preparing perovskite quantum dot glass, in step (4), the annealing time is 2 to 3 hours.

[0014] The purpose of the present invention and the solution to the technical problem are also achieved by adopting the following technical solutions. A perovskite quantum dot glass proposed in the present invention comprises:

[0015] CsPbX3 quantum dots and a glass matrix, wherein the aforementioned CsPbX3 quantum dots are distributed in the aforementioned glass matrix;

[0016] Calculated by oxide mass percentage, the components of the raw materials of perovskite quantum dot glass include: SiO2: 30-40%; H3BO3: 20-30%; ZnO: 15-20%; Cs2CO3: 10-15%; PbX2: 5-10%; and NaX: 5-10%; wherein X is at least one of Cl, Br and I.

[0017] In some embodiments, according to the aforementioned perovskite quantum dot glass, the particle size of the aforementioned CsPbX3 quantum dots is 5 to 10 nm.

[0018] The purpose of the present invention and the technical problem to be solved are also achieved by adopting the following technical solutions. According to the present invention, an optical fiber image transmission element for ultraviolet detection includes:

[0019] Perovskite quantum dot glass layer, coupling agent and optical fiber imaging element;

[0020] The aforementioned perovskite quantum dot glass layer adopts the aforementioned perovskite quantum dot glass;

[0021] The aforementioned coupling agent is disposed between the aforementioned perovskite quantum dot glass layer and the aforementioned optical fiber imaging element to bond the aforementioned perovskite quantum dot glass layer and the aforementioned optical fiber imaging element together.

[0022] The purpose of the present invention and the solution to its technical problems can be further achieved by adopting the following technical measures.

[0023] In some embodiments, according to the aforementioned optical fiber imaging element for ultraviolet detection, the thickness of the aforementioned perovskite quantum dot glass layer is 10 to 50 μm.

[0024] In some embodiments, according to the aforementioned fiber optic imaging element for ultraviolet detection, the aforementioned fiber optic imaging element is a fiber optic panel, a fiber optic light cone or a fiber optic image inverter.

[0025] In some embodiments, according to the aforementioned optical fiber imaging element for ultraviolet detection, the aforementioned coupling agent is epoxy resin glue.

[0026] The purpose of the present invention and the technical problem solved by the present invention are also achieved by adopting the following technical solutions: The present invention proposes the application of any of the aforementioned optical fiber image transmission elements for ultraviolet detection in the field of ultraviolet detection.

[0027] Through the above technical solution, the perovskite quantum dot glass and its preparation method and application of the present invention have at least the following advantages:

[0028] The preparation method of the perovskite quantum dot glass proposed by the present invention is prepared according to the following formula: SiO2: 30-40%; H3BO3: 20-30%; ZnO: 15-20%; Cs2CO3: 10-15%; PbX2: 5-10%; and NaX: 5-10%; wherein X is at least one of Cl, Br and I. After melting the glass raw material, annealing is performed at 350-450°C to induce the in-situ growth of CsPbX3 quantum dots in the glass matrix to obtain the perovskite quantum dot glass. In the perovskite quantum dot glass prepared by the present invention, the outer ring of each perovskite grain is wrapped by an amorphous glass component, which effectively avoids contact with water and oxygen, and improves the long-term stability of the perovskite quantum dots; at the same time, the perovskite quantum dot glass also has high luminous intensity, high quantum yield and wide excitation spectrum, and the perovskite quantum dots can be stimulated to emit light in the ultraviolet band, and can be applied to ultraviolet detectors to achieve efficient detection of ultraviolet light.

[0029] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the following is a detailed description of the preferred embodiments of the present invention in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 is a schematic structural diagram of an optical fiber imaging element for ultraviolet detection disclosed in Example 1 of the present invention;

[0031] Figure 2 is a schematic structural diagram of an optical fiber imaging element for ultraviolet detection disclosed in Example 2 of the present invention;

[0032] Figure 3 is a schematic structural diagram of an optical fiber imaging element for ultraviolet detection disclosed in Example 3 of the present invention;

[0033] Figure 4 It is a fluorescence spectrum diagram of the quantum dot quartz plate and the optical fiber imaging element for ultraviolet detection in Example 1 of the present invention;

[0034] Figure 5 is a fluorescence spectrum diagram of the quantum dot quartz plate and the optical fiber imaging element for ultraviolet detection in Example 2 of the present invention;

[0035] Figure 6 is a fluorescence spectrum diagram of the quantum dot quartz plate and the optical fiber imaging element for ultraviolet detection in Example 3 of the present invention;

[0036] Figure 7 is a fluorescence spectrum diagram of the quantum dot quartz plate and the optical fiber imaging element for ultraviolet detection in Example 4 of the present invention;

[0037] Figure 8 is a fluorescence spectrum diagram of the quantum dot quartz plate and the optical fiber imaging element for ultraviolet detection in Example 5 of the present invention;

[0038] Fig. 9 It is a fluorescence spectrum diagram of the optical fiber imaging element for ultraviolet detection in Example 1 of the present invention and the P20 phosphor optical fiber imaging element in Comparative Example 1;

[0039] Fig.10 This is an X-ray diffraction test diagram of CsPbBr3 quantum dots in Example 1 of the present invention.

[0040] Description of reference numerals:

[0041] 1. Perovskite quantum dot glass layer; 2. Coupling agent; 3. Fiber optic panel; 4. Fiber optic light cone; 5. Fiber optic image inverter. DETAILED DESCRIPTION

[0042] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the following is a detailed description of a perovskite quantum dot glass and its preparation method and its specific implementation, structure, characteristics and effects of the application proposed by the present invention in combination with the accompanying drawings and preferred embodiments. In the following description, different "one embodiment" or "embodiment" does not necessarily refer to the same embodiment. In addition, specific features, structures or characteristics in one or more embodiments may be combined in any suitable form.

[0043] The present invention provides these embodiments to make the present invention thorough and complete, and fully express the scope of the present invention to those skilled in the art. It should be noted that unless otherwise specifically stated, the relative arrangement of the parts and steps, the composition of materials, numerical expressions and numerical values ​​set forth in these embodiments should be interpreted as being merely exemplary, rather than as limiting.

[0044] The present invention provides a method for preparing perovskite quantum dot glass, the steps of which include:

[0045] (1) preparing glass raw materials; the glass raw materials include, by oxide mass percentage, 30-40% SiO2; 20-30% H3BO3; 15-20% ZnO; 10-15% Cs2CO3; 5-10% PbX2; and 5-10% NaX; wherein X is at least one of Cl, Br and I;

[0046] (2) melting the aforementioned glass raw materials to obtain a glass melt;

[0047] (3) pouring the aforementioned glass melt into a mold to obtain a precursor glass; and,

[0048] (4) The aforementioned precursor glass is annealed at 350-450° C. to induce in-situ growth of CsPbX 3 quantum dots in the glass matrix to obtain perovskite quantum dot glass.

[0049] Specifically, the glass raw materials are melted and annealed at 350-450°C to induce the in-situ growth of CsPbX3 quantum dots in the glass matrix to obtain the perovskite quantum dot glass. The chemical reaction equation for the generation of CsPbX3 quantum dots is 2PbX2+2NaX+Cs2CO3=2CsPbX3+Na2CO3. The outer ring of each perovskite grain is wrapped by an amorphous glass component, which effectively avoids contact with water and oxygen, and improves the long-term stability of the perovskite quantum dots.

[0050] CsPbX3 quantum dots have high luminous intensity, high quantum yield, excellent color purity, adjustable band gap and wide excitation spectrum, and they have good chemical stability and high hardness. Using them as ultraviolet light-sensitive materials can achieve high luminous intensity and long-term stability, improve detection efficiency and detection life. In addition, by combining Cl, Br, and I ions, CsPbX3 quantum dots that emit visible light of any wavelength can be prepared, and the combination can be selected according to the actual application scenario.

[0051] In some embodiments, in step (2), the melting temperature is 1000-1100°C.

[0052] Specifically, if the melting temperature is lower than 1000°C, the raw material melts slowly and the efficiency is low; if the melting temperature is higher than 1100°C, the energy consumption is high; therefore, the melting temperature is controlled at 1000-1100°C. The specific melting temperature can be determined according to the types and proportions of Cl, Br, and I in the glass raw materials.

[0053] In some embodiments, in step (4), the annealing time is 2 to 3 hours.

[0054] Specifically, if the annealing time is less than 2 hours, the annealing time is short, and some raw materials have not generated CsPbX3 quantum dots; if the annealing time is greater than 3 hours, the performance of the quantum dot glass will not be further improved; therefore, the annealing time is controlled at 2 to 3 hours.

[0055] The present invention provides a perovskite quantum dot glass, which comprises:

[0056] CsPbX3 quantum dots and a glass matrix, wherein the aforementioned CsPbX3 quantum dots are distributed in the aforementioned glass matrix;

[0057] Calculated by oxide mass percentage, the components of the raw materials of perovskite quantum dot glass include: SiO2: 30-40%; H3BO3: 20-30%; ZnO: 15-20%; Cs2CO3: 10-15%; PbX2: 5-10%; and NaX: 5-10%; wherein X is at least one of Cl, Br and I.

[0058] In some embodiments, the particle size of the aforementioned CsPbX3 quantum dots is 5 to 10 nm.

[0059] The present invention proposes an optical fiber image transmission element for ultraviolet detection, such as Figure 1-3 As shown, it includes:

[0060] Perovskite quantum dot glass layer 1, coupling agent 2 and optical fiber imaging element;

[0061] The aforementioned perovskite quantum dot glass layer 1 adopts the aforementioned perovskite quantum dot glass;

[0062] The aforementioned coupling agent 2 is disposed between the aforementioned perovskite quantum dot glass layer 1 and the aforementioned optical fiber imaging element to bond the aforementioned perovskite quantum dot glass layer 1 and the aforementioned optical fiber imaging element together.

[0063] In some embodiments, the thickness of the aforementioned perovskite quantum dot glass layer 1 is 10-50 μm.

[0064] Specifically, the thickness of the perovskite quantum dot glass layer 1 is controlled within a range of 10 to 50 μm, within which ultraviolet light can be efficiently detected.

[0065] In some embodiments, the aforementioned optical fiber image transmission element is an optical fiber panel 3 , an optical fiber light cone 4 or an optical fiber image inverter 5 .

[0066] In some embodiments, the coupling agent 2 is epoxy resin glue.

[0067] Specifically, the coupling agent 2 can be epoxy resin glue. For example, use a syringe to drop 0.2-0.5 ml of epoxy resin glue at the center of the perovskite quantum dot glass plate, and control the optical fiber imaging element to slowly drop vertically until it is in full contact with the perovskite quantum dot glass plate. At this time, the thickness of the epoxy resin glue is 5-10 μm, and then it is cured for 3-6 hours at 60°C to achieve complete curing. Then, the perovskite quantum dot glass plate is polished to a thickness of 10-50 μm to prepare an optical fiber imaging element for ultraviolet detection.

[0068] The present invention proposes an application of any of the aforementioned optical fiber image transmission elements for ultraviolet detection in the field of ultraviolet detection. For example, the optical fiber image transmission element for ultraviolet detection proposed by the present invention can be installed on an ultraviolet detector for use.

[0069] The present invention will be further described below in conjunction with specific embodiments, but this should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by technicians in this field based on the above-mentioned contents of the present invention still fall within the scope of protection of the present invention.

[0070] Unless otherwise specified, the materials, reagents, etc. involved below are all commercially available products well known to those skilled in the art; unless otherwise specified, the methods described are all methods well known in the art. Unless otherwise defined, the technical terms or scientific terms used should have the common meanings understood by ordinary technicians in the field to which the present invention belongs.

[0071] Embodiment 1:

[0072] This embodiment provides a perovskite quantum dot glass and a preparation method and application thereof.

[0073] (1) preparing glass raw materials; in terms of oxide mass percentage, the glass raw materials include: 30% SiO2; 30% H3BO3; 20% ZnO; 10% Cs2CO3; 5% PbBr2; and 5% NaBr.

[0074] (2) Pour 10 g of high-purity raw material into a mortar and grind for 20 min to fully mix it. Then pour it into a 10 ml crucible and place it in a high-temperature furnace and heat it at 1050° C. for 10 min to obtain a glass melt.

[0075] (3) The glass melt is then poured into a brass mold to obtain a precursor glass.

[0076] (4) Finally, the precursor glass is annealed at 400°C for 2 h to induce the in-situ growth of CsPbBr3 in the glass matrix to obtain CsPbBr3 perovskite quantum dot glass.

[0077] (5) The CsPbBr3 perovskite quantum dot glass is processed into a sheet quantum dot glass with a diameter of 30 mm and a thickness of 1 mm. The coupling agent 2 is epoxy resin glue. Use a syringe to drop 0.2 ml of epoxy resin glue at the center of the sheet quantum dot glass, and control the optical fiber panel 3 to slowly descend vertically until it is in full contact with the quantum dot glass. At this time, the thickness of the epoxy resin glue is 10 μm, and then it is cured at high temperature for 3 hours at 60°C to achieve complete curing. After curing, the quantum dot glass is polished to 20 μm to form a perovskite quantum dot glass layer 1, and an optical fiber imaging element for ultraviolet detection is obtained. Its structural schematic diagram is shown as follows Figure 1 shown.

[0078] (6) The optical fiber panel 3 in step (5) is replaced with a quartz plate to prepare a quantum dot quartz plate.

[0079] The prepared CsPbBr3 quantum dot glass was subjected to X-ray diffraction test, and the results are as follows: Fig.10 As shown in the figure, it can be seen that the peaks correspond to those of the PDF standard comparison card, proving that high-purity CsPbBr3 quantum dots have been successfully synthesized.

[0080] The fluorescence spectrometer was used to test the luminous intensity of the quantum dot quartz plate and the optical fiber imaging element for UV detection. The test results are as follows: Figure 4 As shown, A is a quantum dot quartz plate, and B is an optical fiber imaging element for ultraviolet detection. The peak positions of both are at 530nm and the peaks are sharp, indicating that the sample has high luminous intensity and high purity. The luminous intensity of the quantum dot quartz plate is 100%, and the luminous intensity of the optical fiber imaging element for ultraviolet detection is 80%. The quantum yield of the quantum dot quartz plate is 80%, and the quantum yield of the optical fiber imaging element for ultraviolet detection is 64%.

[0081] Embodiment 2:

[0082] This embodiment provides a perovskite quantum dot glass and a preparation method and application thereof.

[0083] The difference between this embodiment and embodiment 1 is that the optical fiber panel 3 is replaced by an optical fiber light cone 4. The structural schematic diagram of the obtained optical fiber image transmission element for ultraviolet detection is shown in FIG. Figure 2 shown.

[0084] The fluorescence spectrometer was used to test the luminous intensity of the quantum dot quartz plate and the optical fiber imaging element for UV detection. The test results are as follows: Figure 5As shown, A is a quantum dot quartz plate, and B is an optical fiber imaging element for ultraviolet detection. The peak positions of both are at 530nm and the peaks are sharp, indicating that the sample has high luminous intensity and high purity. The luminous intensity of the quantum dot quartz plate is 100%, and the luminous intensity of the optical fiber imaging element for ultraviolet detection is 75%. After coupling the quantum dot glass with the optical fiber light cone 4, the signal intensity loss is 25%, which is 5% more than that of Example 1. This is because the optical fiber light cone 4 is stretched by the optical fiber panel 3, and its own transmittance is worse than that of the optical fiber panel 3, but it still shows strong luminescence. The quantum yield of the quantum dot quartz plate is 80%, and the quantum yield of the optical fiber imaging element for ultraviolet detection is 60%.

[0085] Embodiment 3:

[0086] This embodiment provides a perovskite quantum dot glass and a preparation method and application thereof.

[0087] The difference between this embodiment and embodiment 1 is that the optical fiber panel 3 is replaced by an optical fiber image invertor 5. The structural schematic diagram of the obtained optical fiber image transmission element for ultraviolet detection is shown in FIG. Figure 3 shown.

[0088] The fluorescence spectrometer was used to test the luminous intensity of the quantum dot quartz plate and the optical fiber imaging element for UV detection. The test results are as follows: Figure 6 As shown, A is a quantum dot quartz plate, and B is an optical fiber imaging element for ultraviolet detection. The peak positions of both are at 530nm and the peaks are sharp, indicating that the sample has high luminous intensity and high purity. The luminous intensity of the quantum dot quartz plate is 100%, and the luminous intensity of the optical fiber imaging element for ultraviolet detection is 62%. After coupling the quantum dot glass with the optical fiber image inverter 5, the signal intensity loss is 38%, which is 18% more than that of Example 1. This is because the optical fiber image inverter 5 is twisted by the optical fiber panel 3, and its own optical transmittance is more lost than that of the optical fiber panel 3, but it still shows strong luminescence. The quantum yield of the quantum dot quartz plate is tested to be 80%, and the quantum yield of the optical fiber imaging element for ultraviolet detection is 50%.

[0089] Embodiment 4:

[0090] This embodiment provides a perovskite quantum dot glass and a preparation method and application thereof.

[0091] The difference between this embodiment and embodiment 1 is that the perovskite quantum dot glass in this embodiment is CsPbCl3 perovskite quantum dot glass with a fluorescent color of blue light. In terms of oxide mass percentage, the CsPbCl3 perovskite quantum dot glass ratio is 30% SiO2; 30% H3BO3; 20% ZnO; 10% Cs2CO3; 5% PbCl2; 5% NaCl. 10g of high-purity raw materials are fully mixed and melted in air at 1050°C for 12min to produce a uniform glass melt. The glass melt is then poured into a brass mold to obtain a precursor glass. Finally, the precursor glass is annealed at 400°C for 2h to induce in-situ growth of CsPbCl3 in the glass matrix to obtain CsPbCl3 perovskite quantum dot glass.

[0092] The fluorescence spectrometer was used to test the luminous intensity of the quantum dot quartz plate and the optical fiber imaging element for UV detection. The test results are as follows: Figure 7 As shown, A is a quantum dot quartz plate, and B is an optical fiber imaging element for ultraviolet detection. The peak positions of both are at 450nm and the peaks are sharp, indicating that the sample has high luminous intensity and high purity. The luminous intensity of the quantum dot quartz plate is 100%, and the luminous intensity of the optical fiber imaging element for ultraviolet detection is 80.2%. After coupling the CsPbCl3 quantum dot glass with the optical fiber panel 3, the signal intensity loss is 19.8%. This is because the optical fiber panel 3 has a lower absorption rate in the blue light band, so the luminous intensity loss is less than that of the green light CsPbBr3 quantum dots. The quantum yield of the quantum dot quartz plate is 80%, and the quantum yield of the optical fiber imaging element for ultraviolet detection is 64.2%.

[0093] Embodiment 5:

[0094] This embodiment provides a perovskite quantum dot glass and a preparation method and application thereof.

[0095] The difference between this embodiment and embodiment 1 is that the perovskite quantum dot glass in this embodiment is CsPbI3 perovskite quantum dot glass with a fluorescent color of red light. In terms of oxide mass percentage, the ratio of CsPbI3 perovskite quantum dot glass is 30% SiO2; 30% H3BO3; 20% ZnO; 10% Cs2CO3; 5% PbI2; 5% NaI. 10g of high-purity raw materials are fully mixed and melted in air at 1050°C for 12min to produce a uniform glass melt. The glass melt is then poured into a brass mold to obtain a precursor glass. Finally, the CsPbI3 perovskite quantum dot glass is obtained by heating the precursor glass at 400°C for 2h to induce in-situ growth of CsPbI3 in the glass matrix.

[0096] The fluorescence spectrometer was used to test the luminous intensity of the quantum dot quartz plate and the optical fiber imaging element for UV detection. The test results are as follows: Figure 7 As shown, A is a quantum dot quartz plate, and B is an optical fiber imaging element for ultraviolet detection. The peak positions of both are at 630nm and the peaks are sharp, indicating that the sample has high luminous intensity and high purity. The luminous intensity of the quantum dot quartz plate is 100%, and the luminous intensity of the optical fiber imaging element for ultraviolet detection is 79.7%. After coupling the CsPbI3 quantum dot glass with the optical fiber panel 3, the signal intensity loss is 20.3%. This is because the optical fiber panel 3 has a strong absorption rate in the red light band, so the luminous intensity loss of the CsPbBr3 quantum dots is greater than that of the green light. The quantum yield of the quantum dot quartz plate is 80%, and the quantum yield of the optical fiber imaging element for ultraviolet detection is 63.2%.

[0097] Comparative Example 1:

[0098] The photosensitive material uses ordinary green phosphor P20 purchased on the market. P20 phosphor is dispersed in anhydrous ethanol to prepare a phosphor solution. The same optical fiber panel 3 as in Example 1 is used, 0.2 ml of phosphor solution is dripped on the surface of the optical fiber panel 3, and the rotation speed is controlled to 800 rpm by spin coating for 60 seconds. After spin coating, it is heated at 60°C in an oven for 30 minutes, and repeated three times to form a phosphor film with a thickness of 20 microns on the surface of the optical fiber panel 3, and a P20 phosphor optical fiber imaging element is obtained.

[0099] The fluorescence spectra of the ultraviolet detection optical fiber imaging element in Example 1 and the above-mentioned P20 phosphor optical fiber imaging element were tested using a fluorescence spectrometer. The test results are as follows: Fig. 9 As shown. Compared with Example 1, the luminous intensity of the ultraviolet detection optical fiber imaging element using P20 phosphor as the photosensitive material is low and the half-peak width is large, indicating that the luminous intensity of the phosphor is weak and the luminous purity is low. The quantum yield of the P20 phosphor optical fiber imaging element was tested and its quantum yield was 30%, which is much lower than the quantum yield of 64% of the CsPbBr3 quantum dot glass after coupling in Example 1.

[0100] The technical features in the claims and / or the specification of the present invention may be combined, and the combination is not limited to the combination obtained by reference in the claims. The technical solution obtained by combining the technical features in the claims and / or the specification is also within the protection scope of the present invention.

[0101] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A method for preparing perovskite quantum dot glass, characterized in that: The steps include: (1) preparing glass raw materials; the glass raw materials include, by oxide mass percentage, 30-40% SiO2; 20-30% H3BO3; 15-20% ZnO; 10-15% Cs2CO3; 5-10% PbX2; and 5-10% NaX; wherein X is at least one of Cl, Br and I; (2) melting the glass raw materials to obtain a glass melt; (3) pouring the glass melt into a mold to obtain a precursor glass; and, (4) The precursor glass is annealed at 350-450° C. to induce in-situ growth of CsPbX3 quantum dots in the glass matrix to obtain perovskite quantum dot glass.

2. The preparation method according to claim 1, characterized in that: In step (2), the melting temperature is 1000-1100°C.

3. The preparation method according to claim 1, characterized in that: In step (4), the annealing time is 2 to 3 hours.

4. A perovskite quantum dot glass, characterized in that: It includes: CsPbX3 quantum dots and a glass matrix, wherein the CsPbX3 quantum dots are distributed in the glass matrix; Calculated by oxide mass percentage, the components of the raw materials of perovskite quantum dot glass include: SiO2: 30-40%; H3BO3: 20-30%; ZnO: 15-20%; Cs2CO3: 10-15%; PbX2: 5-10%; and NaX: 5-10%; wherein X is at least one of Cl, Br and I.

5. The perovskite quantum dot glass according to claim 4, characterized in that: The particle size of the CsPbX3 quantum dots is 5 to 10 nm.

6. An optical fiber image transmission element for ultraviolet detection, characterized in that: It includes: Perovskite quantum dot glass layer, coupling agent and optical fiber imaging element; The perovskite quantum dot glass layer adopts the perovskite quantum dot glass described in claim 4; The coupling agent is arranged between the perovskite quantum dot glass layer and the optical fiber imaging element to bond the perovskite quantum dot glass layer and the optical fiber imaging element together.

7. The optical fiber image transmission element for ultraviolet detection according to claim 6, characterized in that: The thickness of the perovskite quantum dot glass layer is 10 to 50 μm.

8. The optical fiber image transmission element for ultraviolet detection according to claim 6, characterized in that: The optical fiber image transmission element is an optical fiber panel, an optical fiber light cone or an optical fiber image invertor.

9. The optical fiber image transmission element for ultraviolet detection according to claim 6, characterized in that: The coupling agent is epoxy resin glue.

10. Application of the optical fiber imaging element for ultraviolet detection according to any one of claims 6 to 9 in the field of ultraviolet detection.

Citation Information

Patent Citations

  • Ultraviolet detecting system based on doped quantum dot wavelength conversion and method thereof

    CN108123008A

  • Method for promoting crystallization of all-inorganic perovskite quantum dots in glass by adding fluoride

    CN110194593A

  • Full-inorganic perovskite quantum dot fluorescent glass as well as preparation method and application thereof

    CN113912291A

  • Inorganic perovskite quantum dot glass and preparation method thereof

    CN115849721A